Oracle database 11g building Oracle XML DB applications - Wang, Jinyu 1972- (New York McGraw-Hill, 2011)
"Master the XML Programming Features in Oracle Database 11gDevelop, debug, and administer data-backed XML applications using the expert instruction and best practices in this Oracle Press guide. Oracle Database 11g: Building Oracle XML DB Applications discusses the latest development tools, technologies, and components. Find out how to set up Oracle XML Database (Oracle XML DB), build XML applications in Oracle JDeveloper 11g, work with XSLT stylesheets, and incorporate full-text search. Troubleshooting, performance tuning, and security are also covered in this comprehensive resource. Create, store, and query XMLtypes using Oracle XML DB Load XML documents into relational tables and define SQL views Parse and validate schema with Oracle XDK for Java and PL/SQL packages Merge documents, generate reports, and transform data using XSLT Construct applications from Oracle XML DB Web services Use Oracle JDeveloper 11g to design and deploy XML applications Integrate Oracle Text and Oracle Secure Enterprise Search features Streamline the development process using Oracle Application Express "--Provided by publisher.
"Develop, debug, and administer data-backed XML applications using the expert instruction and best practices in this Oracle Press guide. Oracle Database 11g: Building Oracle XML DB Applications discusses the latest development tools, technologies, and components. Find out how to set up Oracle XML Database, build XML applications in Oracle JDeveloper 11g, work with XSLT stylesheets, and incorporate full-text search. Troubleshooting, performance tuning, and security are also covered in this comprehensive resource"--Provided by publisher.
Machine generated contents note: Part I: Basic Concepts and Technologies -- Chapter 1: Oracle XML DB Overview -- Chapter 2: Basic XML Concepts -- Chapter 3: XMLType -- Chapter 4: XML DB Repository -- Chapter 5: Parsing XML -- Chapter 6: Validating XML -- Chapter 7: Accessing XML with Xpath -- Chapter 8: Transforming XML -- Chapter 9: Querying XML -- Chapter 10: Creating XML from Relational Tables -- Chapter 11: Searching XML -- Part II: Managing Oracle XML Database (XML DB) -- Chapter 12: Oracle XML DB Installation -- Chapter 13: XML DB Storage -- Chapter 14: XML DB Backup and Recovery -- Chapter 14: XML DB Security -- Chapter 15: XML DB Performance Tuning -- Part III: Building XML Applications -- Chapter 16: XML DB Web Services -- Chapter 17: XML DB Support in Oracle Jdeveloper -- Chapter 18: Pulling It All Together: Sample Application -- Appendices -- Appendix A: Oracle Secure Enterprise Search Installation -- Appendix B: Oracle Application Express Installation -- Appendix C: Oracle XML DB Cheat sheet.
Includes index.
Keywords: Oracle (Computer file).; XML (Document markup language); Relational databases; Database management